A Dual‐Functional Conductive Framework Embedded with TiN‐VN Heterostructures for Highly Efficient Polysulfide and Lithium Regulation toward Stable Li–S Full Batteries. Issue 6 (12th December 2019) - Yao, Yu; Wang, Haiyun; Yang, Hai; Zeng, Sifan; Xu, Rui; Liu, Fanfan; Shi, Pengcheng; Feng, Yuezhan; Wang, Kai; Yang, Wenjin; Wu, Xiaojun; Luo, Wei; et al.
Abstract: Lithium–sulfur (Li–S) batteries are strongly considered as next‐generation energy storage systems because of their high energy density. However, the shuttling of lithium polysulfides (LiPS), sluggish reaction kinetics, and uncontrollable Li‐dendrite growth severely degrade the electrochemical performance of Li–S batteries. Herein, a dual‐functional flexible free‐standing carbon nanofiber conductive framework in situ embedded with TiN‐VN heterostructures (TiN‐VN@CNFs) as an advanced host simultaneously for both the sulfur cathode (S/TiN‐VN@CNFs) and the lithium anode (Li/TiN‐VN@CNFs) is designed. As cathode host, the TiN‐VN@CNFs can offer synergistic function of physical confinement, chemical anchoring, and superb electrocatalysis of LiPS redox reactions. Meanwhile, the well‐designed host with excellent lithiophilic feature can realize homogeneous lithium deposition for suppressing dendrite growth. Combined with these merits, the full battery (denoted as S/TiN‐VN@CNFs || Li/TiN‐VN@CNFs) exhibits remarkable electrochemical properties including high reversible capacity of 1110 mAh g −1 after 100 cycles at 0.2 C and ultralong cycle life over 600 cycles at 2 C. Even with a high sulfur loading of 5.6 mg cm −2, the full cell can achieve a high areal capacity of 5.5 mAh cm −2 at 0.1 C. This work paves a new design from theoretical and experimental aspects for fabricating high‐energy‐density flexible Li–S full batteries. Abstract : A dual‐functional flexible free‐standing carbon nanofiber conductive framework in situ embedded with TiN‐VN heterostructures (TiN‐VN@CNFs) is designed as an advanced host simultaneously for both the sulfur cathode and the lithium‐metal anode in Li–S batteries. The assembled Li–S full battery exhibits superior electrochemical performance due to the enhanced sulfur utilization and highly reversible lithium stripping/plating behavior.